Poly[μ(2)-aqua-μ(4)-(2-{3-[(6-chloropyridin-3-yl)methyl]-2-oxoimidazolidin-1-yl}acetato)-sodium] - Kant, Rajni (International Union of Crystallography, 2012)
In the title compound, [Na(C(11)H(11)ClN(3)O(3))(H(2)O)](n), there are two independent Na(I) ions, one of which lies on an inversion center and is coordinated in a slightly distorted octahedral environment. The other Na(I) ion lies on a twofold rotation axis and is cooordinated in a slightly distorted trigonal–bipyramidal coordination environment. In the organic ligand, the imidazolidine ring adopts a half-chair conformation. The Na(I) ions bridge organic ligands and water molecules, forming a two-dimensional structure parallel to (100). There are intermolecular O—H⋯O and weak C—H⋯O hydrogen bonds within the two-dimensional structure.